Dual Role of CRABP2 in Colorectal Cancer: Oncogenesis via Nuclear RB1 and Cytoplasmic AFG3L2/SLC25A39 Axis, While Limiting Liver Metastasis through Cytoplasmic AFG3L2/PINK1/Parkin‐Mediated Mitophagy - Chuanxin Tian; Sheng Yang; Chuan Zhang; Renzhong Zhu; Chen Chen; Xiaowei Wang; Dongsheng Zhang; Qingyang Sun; Hengjie Xu; Hongxu Nie; Yue Zhang; Dongjian Ji; et al. (Advanced Science)
Abstract Colorectal cancer (CRC) progression and metastasis involve numerous regulatory factors. Among these, cellular retinoic acid‐binding protein 2 (CRABP2) has been implicated as both a tumor activator and suppressor. Here, it is aimed to clarify the role of CRABP2 in CRC growth and metastasis and explore the underlying molecular mechanisms mediating its cellular functions. Using both in vitro and in vivo models, including a colonocyte‐specific CRABP2 conditional knockout mouse model (Crabp2ΔIEC) and a subcutaneous tumorigenesis assay in BALB/c nude mice, it is shown that nuclear CRABP2 enhances tumor growth by interacting with and downregulating the tumor suppressor RB1, whereas cytoplasmic CRABP2 suppresses CRC liver metastasis by interacting with AFG3L2 and promoting mitophagy. In addition, the AFG3L2–SLC25A39 axis is identified as a distinct mechanism by which cytoplasmic CRABP2 increases mitochondrial glutathione stability to promote cell proliferation independent of the nuclear RB1 pathway. Notably, analysis of tissue from CRC patients reveals that CRABP2 protein has distinct prognostic implications and functional roles in the progression and metastasis of CRC dependent on its subcellular localization. Ultimately, by elucidating the role of CRABP2 in CRC, it is aimed to provide new insight into disease pathogenesis and inform the development of therapeutic interventions.